Hermeneutika Al-Qur'an dan Debat Tafsir Modern: Implementasinya dengan Masa Kini - Rif'atul Khoiriah Malik (Universitas Nurul Jadid, 2019)
The interpretation of the Quran which triggered controversial themes in the post-modern era is now an interesting study to be studied. As in this paper, hermeneutics as a new method of interpretation that emerged in Ancient Greece has become part of the interpretation method of the Quran. From this arises a debate over the emergence of the hermeneutical method if applied to the Quran. Will the hermeneutic approach be used in the interpretation of the Quran? How does hermeneutics answer the modern interpretation debate? From this question, the author examines some views on hermeneutics among interpreters, accompanied by the interpretation of several controversial themes that occur in modern societies. Through this paper, it will be seen that, the knowledge that continues to be a reformer in the modern era is something that should not be excluded or rejected. With the aim of scientific upgrading, it is increasingly evolving in time and places, but from that it does not forget the old traditions of returning to the Quran and Hadith. Keywords: Hermeneutics, Alquran, Modern Interpretation.